The Analysis of c-silica Dust Content in Respirable Dust in the Ceramic Industry - Moch. Sahri; Merry Sunaryo (Universitas Airlangga, 2020)
Introduction: Exposure to hazards in the work environment in the ceramic industry includes silica dust and heat temperatures. The purpose of this research was to analyze the respirable dust and c-silica dust, in addition to calculate c-silica dust in respirated dust. In addition, an evaluation of the results of dust measurements was also carried out by comparing it to the threshold value. Method: This was a descriptive study by testing samples of respirable dust and c-silica dust in the work place. The research was conducted at one of the ceramic industries in East Java. Data collection was carried out on all workers in the production division of 39 peoples. The measurement method for respirable dust analysis used the gravimetric method based on NIOSH method (NMAM 0600, 1998), while the analysis of c-silica dust used XRD equipment in accordance with the NIOSH method (NMAM 7500, 2003). Results: The results of the measurement of respirable dust in 39 respondents obtained a range of values of 0.019 - 0.0563 mg/m3 with an average of 0.19 mg/m3, while for c-silica dust, the results were at the range of 0.0020 - 0.3129 mg/m3 with an average of 0.07 mg/m3. The percentage of c-silica dust content in the ceramics industry in residential dust is different by 5 - 74.3% with the average of 34.89%. Conclusion: Evaluation of the results of measurement of respirable dust found that all samples were below the threshold value, while for c-silica dust, there were 27 samples with values above the threshold. On the average, there is 34.89% level of c-silica in respirable dust in the ceramic industry.Keywords: ceramic industry, c-silica, respirable dust